2013
DOI: 10.5799/ahinjs.01.2013.04.0347
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and primary healthcare

Abstract: Diabetes mellitus is a metabolic disease characterized by hyperglycemia. It stems from defects, which are formed in insulin secretion, insulin effect or both caused by interactions of genetics, environmental factors and life style changes. As well as being a very serious and progressive disease, we face it as a major health problem for both individuals and society for it adversely affects the mortality and morbidity by causing chronic and acute complications in case of lack of control.Maximum effort should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Çalışmadaki hastaların, çoğunluğunun 50 yaşın üzerinde (%60) ve 10 yıldan fazla diyabet hastası (%40) olduğu görüldü. Bu bulgular, literatür sonuçları ile benzerlik gösterdiği ve Tip 2 DM hastalığının çoğunlukla 30 yaşlarından sonra tanısı konulduğu belirtildi (19) . Marcus MD.…”
Section: Discussionunclassified
“…Çalışmadaki hastaların, çoğunluğunun 50 yaşın üzerinde (%60) ve 10 yıldan fazla diyabet hastası (%40) olduğu görüldü. Bu bulgular, literatür sonuçları ile benzerlik gösterdiği ve Tip 2 DM hastalığının çoğunlukla 30 yaşlarından sonra tanısı konulduğu belirtildi (19) . Marcus MD.…”
Section: Discussionunclassified
“…Down syndrome is a metabolic disease that is among the genetic syndromes associated with diabetes mellitus. When the causes are examined, it is caused by disorders caused by insulin secretion due to differences in genetics, environmental factors and lifestyles (Tanrıverdi, Çelepkolu and Aslanhan, 2013). The number of meals of individuals included in the research is shown in figure 3.…”
Section: Continuous Diseases Of the Individualsmentioning
confidence: 99%
“…Ayrıca hastalara diyabetin komplikasyonları hakkında bilgilendirme, tedavinin amacının ne olduğu, beslenme ve egzersiz hakkında bilgilendirme, kan şekerinde ki değişikliklerde nasıl semptomlar olabileceği ve ne yapması gerektiği hakkında bilgi verme, ayaklarını kuru tutması gerektiği parmak aralarının günde 4-5 defa çatlaklıklar, yara varlığının kontrolü açısından bakması gerektiği kendisine ve primer ilgilenen yakınına öğretilmelidir. Hastaların bu eğitim programına ne kadar uydukları ve genel diyabet takibinin yapılabilmesi için belli aralıklarla kontrole çağırmakta da fayda vardır [32].…”
Section: Diyabetik Ayaklı Hastanın Eğitimiunclassified